Hybrid vs Traditional models on customer experience : an application to the Portuguese Real Estate Market - Gonçalves, Marta de Sousa (2018)
Technology is impacting industries all over the world and the real estate industry is no exception. This thesis aims to analyze the traditional model of real estate and the new emerging methods where several tasks are performed online (reducing the human contact) and understand the current customer experience with the goal to understand how technology can improve it. Several research methods were used to obtain data. In terms of qualitative search, a focus group was conducted to people who already interacted with the market and 3 in-depth interviews were performed to Millennials with no experience in the real estate industry. The quantitative data was gathered through a survey conveyed to 468 valid participants. Both searches were reinforced by literature on the real estate market, the impact of technology in the industry, customer experience, brand equity and a description of the two generations under study: Millennials and Generation X. The key findings suggest that the overall satisfaction with the mediation process regarding quickness, smoothness and the method chosen is between average and great. There is a considerable number of participants that do not perceive the need for a mediator. There is a limited knowledge of the market. The preferences in the market are not aligned as there are significant differences between sellers and buyers and between generations. To conclude, for Millennials, a hybrid model provides a better customer experience while for Generation X, a traditional model is the one with a superior level on experience.